INNOVATIVE EUROPEAN PRACTICES OF DIGITALIZATION AS A KEY FACTOR IN ENSURING SOCIO-ECONOMIC SECURITY IN THE CONTEXT OF GLOBAL CHALLENGES - Cherep, Alla; Voronkova, Valentyna; Cherep, Oleksandr (Socio-economic relations in the digital society, 2024)
The purpose of the article is to develop a concept for implementing innovative European digitalization practices as a key factor in ensuring socio-economic security in the context of global challenges. Using the methods of risk-oriented approach, system analysis and modelling, the ways of using innovative European digitalization practices are considered. Research results: 1. The problems that arise in the modern analysis of the relationship between digitalization and socio-economic security are diagnosed. 2. The directions of technology development that can significantly improve socio-economic security are analyzed. Global challenges, such as pandemics, economic crises, and climate change, can significantly affect the processes of digitalization and their impact on socio-economic security. The scientific novelty of the study is that European digitalization practices are an important tool in ensuring socio-economic security in the face of global challenges, and therefore it is important to explore the latest approaches that can be offered for sustainable development. It has been proven that AI can analyze large amounts of data to predict economic crises, natural disasters, or social conflicts, allowing governments and companies to prepare for possible challenges in advance; using AI to optimize production, logistics, and resource management helps reduce costs and increase economic resilience. Cloud solutions provide access to important resources and services from anywhere in the world, which ensures the uninterrupted operation of businesses and government agencies in case of emergencies. Cloud platforms provide effective management of large amounts of data, which is necessary for strategic decision-making. The practical significance of the study is to overcome key challenges and use opportunities for further implementation of innovative European digitalization practices as a key factor in ensuring socio-economic security in the face of global challenges. The use of innovative European practices has a significant potential to accelerate the achievement of the SDGs but requires taking into account possible risks and challenges.